2017
DOI: 10.1097/mao.0000000000001309
|View full text |Cite
|
Sign up to set email alerts
|

Otolith Dysfunction in Persons With Both Diabetes and Benign Paroxysmal Positional Vertigo

Abstract: Objective-Vestibular dysfunction is a well-recognized complication of type 2 diabetes (DM) that may contribute to increased fall risk. The prevalence of benign paroxysmal positional vertigo (BPPV) is higher in people with DM. The impact of DM on the otolith organs of the vestibular system in people with BPPV is unknown. The purpose of this study was to analyze otolith function using vestibular evoked myogenic potential (VEMP) tests in people with DM and concurrent BPPV (BPPV+DM), and to examine the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…While a recent study did not find differences in any of the cVEMP parameters between PCBPPV patients and matching healthy controls (27), most previous publications have reported rates of abnormal cVEMPS within the range of 23.5-39% (4,30,(33)(34)(35)(36)(37)(38)(39)(40). The higher occurrence of pathological cVEMP previously found might stem from the different criteria employed.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…While a recent study did not find differences in any of the cVEMP parameters between PCBPPV patients and matching healthy controls (27), most previous publications have reported rates of abnormal cVEMPS within the range of 23.5-39% (4,30,(33)(34)(35)(36)(37)(38)(39)(40). The higher occurrence of pathological cVEMP previously found might stem from the different criteria employed.…”
Section: Discussionmentioning
confidence: 76%
“…The higher occurrence of pathological cVEMP previously found might stem from the different criteria employed. While in ours and other studies (26) the normalized criterion of increased IAD and missing cVEMP responses were the parameters taken into consideration, others used in addition the less conservative criteria of prolonged wave latencies and decreased amplitudes (30,(33)(34)(35)(36)(37)(38)(39)(40). Also, two of the studies (33,39) included lateral and anterior canal variants of BPPV while the reported cVEMP results did not distinguish between the groups.…”
Section: Discussionmentioning
confidence: 87%
“…The selected articles did not explain the relationship of high BMI (obesity) with changes in PB. However, literature describes the association of obesity with DM2 due to the increased release of substances such as fatty acids not esterified by adipose tissue, which Among the five articles reviewed in this study, two 16,17 cited the systemic arterial hypertension (SAH) variable and, in both, diabetic individuals with PB alteration had a higher frequency of this disease. SAH causes an increase in blood pressure levels that leads to functional and/or structural alterations in some organs and may lead to impairment of capillary blood flow and oxygen transport 21,22 .…”
Section: Iibmentioning
confidence: 96%
“…High body mass index (BMI) was described in three articles 17,18,20 , showing a population with high a BMI average, above 30 Kg/m 2 , in relation to the other groups. According to the World Health Organization, a BMI equal to or above 30 Kg/m 2 is characterized as obese 24 .…”
Section: Iibmentioning
confidence: 99%
“…However, oVEMP (i.e., utricle function) abnormalities were not observed, demonstrating further discrepancies in the literature. 34 There is pathophysiologic evidence suggesting a direct effect of DM on the vestibular system, epidemiological evidence linking DM and vestibular loss and falls risk, but the clinical evidence in patient populations is far from conclusive. There is no consistent pattern of test results with some suggesting greater loss in the SCC, others suggesting intact SCC with impairments observed in the otolith end organs, and multiple combinations thereof.…”
Section: Clinical Evidence Of Diabetes and Vestibular Loss: Laboratormentioning
confidence: 99%